Relationships among soluble phenolics, insoluble proanthocyanidins and fiber in East African browse species - Reed, J.D. (1986)
Discusses the behaviour of phenolics and tannins in the detergent systems of forage analysis in relation to estimating the nutritive value of 17 East African browse species; presents the results of the analysis, i.e. neutral detergent fiber (NDF), soluble phenolics and insoluble proanthocyanidins (condensed tannins).